2006
DOI: 10.1007/s00330-006-0318-y
|View full text |Cite
|
Sign up to set email alerts
|

New coil concept for endoluminal MR imaging

Abstract: Our aim was to conduct a prospective study to evaluate staging accuracy of a new coil concept for endoluminal magnetic resonance imaging (MRI) on ex vivo gastric carcinomas. Twenty-eight consecutive patients referred to surgery with a clinically proven primary gastric malignancy were included. Surgical specimens were examined with a foldable and self-expanding loop coil (8-cm diameter) at 1.5 Tesla immediately after total gastrectomy. T1-and T2-weighted and opposed-phase sequences (axial, frontal sections; 3-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The use of both an external and endoluminal coil has been previously advocated to improve staging of perioesophageal lymph nodes which may be beyond the imaging range of the endoluminal probe [5]. A recent ex vivo study assessing the local staging of gastric carcinoma using an endoluminal technique shows promise by employing a folding, self-expanding 8-cm diameter receiver coil, again to improve the imaging range whilst maintaining high spatial resolution [12].…”
Section: Discussionmentioning
confidence: 97%
“…The use of both an external and endoluminal coil has been previously advocated to improve staging of perioesophageal lymph nodes which may be beyond the imaging range of the endoluminal probe [5]. A recent ex vivo study assessing the local staging of gastric carcinoma using an endoluminal technique shows promise by employing a folding, self-expanding 8-cm diameter receiver coil, again to improve the imaging range whilst maintaining high spatial resolution [12].…”
Section: Discussionmentioning
confidence: 97%
“…One of the shortcomings of this study was that the diagnosis of postoperative abdominal lymph node metastasis was dependent on regular abdominal enhanced CT, MRI, and PET-CT imaging. However, CT diagnosis of abdominal lymph nodes has an overall accuracy of 62–64% [ 18 ] and MRI has sensitivity of 71% ± 18.22, specificity of 29% ± 18.07, and accuracy of 58% ± 19.72 in this regard [ 19 ]. PET/CT for diagnosis of abdominal LN metastasis has the sensitivity, specificity, positive predictive value (PPV) and negative predictive value of FDG of 40%, 95%, 91% and 56%, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the coaxial cable will also be inserted inside the patient's body it could burn tissues. To overcome this problem, promising preliminary studies have demonstrated the potential of optical fibers to transmit and receive RF signals to prevent burns …”
Section: Discussionmentioning
confidence: 99%